Elbow Joint Angles in Elbow Flexor Unilateral Resistance Exercise Training Determine Its Effects on Muscle Strength and Thickness of Trained and Non-trained Arms - Sato, Shigeru; Yoshida, Riku; Kiyono, Ryosuke; Yahata, Kaoru; Yasaka, Koki; Nunes, João Pedro; Nosaka, Kazunori; Nakamura, Masatoshi (Frontiers in Physiology, 2021)
The present study compared two unilateral arm curl resistance exercise protocols with a different starting and finishing elbow joint angle in the same ROM for changes in elbow flexors strength and muscle thickness of the trained and non-trained arms. Thirty-three non-resistance trained young adults were randomly assigned to one of the three groups: extended joint training (0°-50°; EXT, n=12); flexed joint training (80°-130°; FLE, n=12); and non-training control (n=8). The exercise training was performed by the dominant arms twice a week for 5 weeks with gradual increases in the training volume over 10 training sessions, and the non-dominant (non-trained) arms were investigated for the cross-education effect. Maximal voluntary contraction torque of isometric (MVC-ISO), concentric (MVC-CON), and eccentric contractions (MVC-ECC), and thickness (MT) of biceps brachii and brachialis of the trained and non-trained arms were assessed at baseline and 4-8 days after the last training session. The control group did not show significant changes in any variables. Significant (P<0.05) increases in MVC-ISO torque (16.2±12.6%), MVC-CON torque (21.1±24.4%), and MVC-ECC torque (19.6±17.5%) of the trained arm were observed for the EXT group only. The magnitude of the increase in MT of the trained arm was greater (P<0.05) for EXT (8.9±3.9%) than FLE (3.4±2.7%). The cross-education effect was evident for MVC-ISO (15.9±14.8%) and MVC-CON (16.7±20.0%) torque of the EXT group only. These results suggest that resistance training at extended elbow joint induces greater muscle adaptations and cross-education effect than that at flexed elbow joint.